Dynamics of Area, Production, Productivity and Export of Rice in India - Rudrapur, Shreeshail; Hiremath, Deepa (International Journal of Economic Plants, 2025)
The study was conducted for the period of 20 years (2004–05 to 2023–24) and over 15 years (2008–09 to 2022–23) for its exportto know the growth rate and instability in area, production and productivity of rice.The study was based on secondary data. The data was collected from different e-resources. Compound annual growth rate and instability index analysis were used for the analysis and interpretation of the results.The major findings of the study showed that the growth rate in productivity was higher than the growth rate in area under rice cultivation. A low instability index indicated that the area, production and productivity of rice were relatively stable with minimal fluctuations. The study also revealed that the export of both basmati and non-basmati rice showed significant positive growth rate. The growth rate and instability in export of non-basmati rice were found to be more than the growth rate in basmati rice. India is the major producer of basmati rice, Indian farmers and traders need to make use of this opportunity to earn more profit through the production of quality product, its standardisation and market diversification. Export earnings of rice is the major source of foreign exchange as far as agriculture commodities are concerned that stabilises the balance of payment of the country and hence Indian export policies need to encourage the farmers in producing and supplying export quality basmati and non basmati rice by reducing export restriction, streamlining export procedures and addressing quality concerns.